A Kantian perspective on moral duty concerning far distant generations: from noumenal freedom to phenomenal law - Morán Roa, Alberto (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article carries out a Kantian reading of our possible duties towards future generations. The moral value of this discussion, which at present cannot be dissociated from the phenomenon of climate change, will be analysed under three headings: a comparison with the aesthetically sublime feeling of Enthusiasmus, an assessment of the possibility of establishing moral duties towards an indeterminate object, and a study of the role of culture in moral progress. The possibility of such moral guidance promoting action will then be considered: the obstacles in this respect show the necessity of shifting the discussion of duties towards future generations from the moral to the legal sphere, where Kantian theory shows great potential. This wide-ranging view finally aims to highlight the role of interrelation and co-determination in Kantian dynamic thought.